Environmental Governance in Handling Flood Problems in Makassar City - Handam, Handam (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Environmental management or Environmental Governance is a comprehensive approach that involves various stakeholders in decision-making, policy formulation, and implementation of strategies to address environmental problems. In the context of Makassar City, this approach is crucial in managing the increasing risk of flooding due to climate change, changes in land use, and population growth. This study highlights the effectiveness of flood management policies based on community participation, information transparency, and coordination between institutions. The survey results show that the majority of the community feels that flood management policies are not yet effective, with low levels of participation. In addition, the lack of transparency and coordination between institutions are major obstacles in the implementation of flood mitigation policies. This study recommends improving the participatory and collaborative approach in Environmental Governance, by integrating ecosystem-based policies, strengthening the role of the community, and increasing the use of sustainable infrastructure to create city resilience to future flood disasters.